Peran Regulasi Diri dalam Belajar terhadap Prokrastinasi Akademik pada Siswa Madrasah Tsanawiyah (Jurnal Psikologi Integratif, 2023)
Academic procrastination is a detrimental behavior, including in the context of students at Madrasah Tsanawiyah. This study aims to analyze the role of self-regulated learning towards academic procrastination in Madrasah Tsanawiyah students. The study population was students from class VII to class IX at Madrasah Tsanawiyah IB, totaling 215 students consisting of 111 male students and 104 female students. Determination of research samples using cluster random sampling technique and obtained a sample of 140 students. The research data was obtained using a self-regulation scale in learning with a reliability value of 0.899 and an academic procrastination scale with a reliability value of 0.903. Simple linear regression was chosen as the research data analysis. Based on the results of the analysis it is known that self-regulation in learning is negatively related to academic procrastination with a regression coefficient of -0.817 with a value of p = 0.000 (p
Keywords: Prokrastinasi Akademik; Self Regulated Learning; Siswa Madrasah